Analisis Ability to Pay Mahasiswa Politeknik Sahid Jakarta - Nicko Gana Saputra; Reni Sulistyowati; Angga Pardosi (Politeknik Sahid, 2020)
Sahid Polytechnic is one of the universities in the field of tourism that has been established since 1983 under the part of the Sahid Jaya Education and Social Foundation. Along with the development of tourism education in Indonesia, causing more and more new universities so that the Sahid Polytechnic must compete fiercely to find new students. In 2019 the number of students at the Sahid Polytechnic is 1,431 students. This study was conducted to analyze the students' ability to pay for tuition at the Sahid Polytechnic in Jakarta, and there needs to be an increase in the priority of the service dimensions of the Sahid Polytechnic management, including the satisfaction of obtaining services from Sahid Polytechnic staff, security and comfort in the campus area and ease in obtaining campus facilities. The method of collecting data by distributing questionnaires to Sahid Polytechnic students with sampling using the Slovin method so that 93 students were obtained as respondents. Ability To Pay measurements use the household budget method. The results of the study were the estimated average ATP value of Rp.1,530,322, - with a median of Rp. 1,500,000. The biggest ATP of students is in the scenario between Rp.750,000 - Rp. 1,150,000 as much as 86%. By increasing the priority dimensions expected by students, ATP from Sahid Polytechnic students will increase.